Effect of some metal salts on the cultivable part of soil microbial assemblage in a calcareous loam cropland 6 years after contamination - Szili-Kovács, Tibor (Acta Biologica Szegediensis, 2008)
Heavy metal contamination is of great interest because of the accumulation in soil and a potential risk to get into the food chain. Effect of three heavy metal salts added to field plots on the soil microbial assemblage and their total biomass was investigated 6 years after the artificial contamination. The metal addition was 90 and 810 kg per hectare for cadmium, copper and nickel on a calcareous loamy chernozem soil. Cadmium at 90 and 810 kg ha-1 rates resulted in 80 and 670-fold increase; copper 2 and 9-fold increase; nickel 2 and 6-fold increase to the background level. Number of Actinobacteria and Azotobacter spp decreased while oligotrophic bacteria and microscopic fungi increased due to the metal additions especially in the case of cadmium. This indicated structural changes in soil microbial assemblage. Soil microbial biomass C was significantly lower in all metal treated soils compared to the control, but the higher doses did not result in further depletion.